Alkali-activated gelling composition, slag material and application thereof
By adding silicon calcium slag to the slag powder and fly ash stimulated by sodium carbonate, the slag powder is synergistically stimulated, and the problems of slow hydration rate and low strength in the existing technology are solved, and efficient early mechanical performance improvement and solidification are achieved Waste utilization reduces material costs and environmental hazards.
Patent Information
- Application Number
- CN202411097244.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-09
AI Technical Summary
The early hydration rate of existing alkali-activated slag materials is slow and has low strength. The use of strong alkali-activated slag materials leads to high cost, difficult to regulate their workability, and high alkalinity can cause harm to the human body and the environment.
By adding silicon calcium slag to slag powder and fly ash stimulated by weak alkaline sodium carbonate, the slag powder is synergistically stimulated by sodium carbonate and silicon calcium slag, and the early mechanical properties of the gelled materials are improved.
It significantly improves the early compressive strength of gelled materials, reduces material costs, avoids the harm of high alkalinity to the environment and the human body, and improves the utilization rate of solid waste.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gelling materials, and in particular relates to an alkali-activated gelling composition, a slag material and applications thereof. Background Art
[0002] Alkali-activated cementitious materials based on solid wastes such as slag, fly ash, and steel slag have become one of the important cement substitutes. Alkali-activated cementitious materials can absorb solid wastes, effectively alleviate the problems of land occupation and pollution caused by them, and have lower carbon emissions than cement. However, volcanic ash materials such as slag and fly ash as matrix materials generally have the problem of low hydration activity and generally need to be used with alkaline activators.
[0003] The slow early hydration rate and low strength have always been the main problems of weak base activated slag materials such as sodium carbonate. In response to this, the existing technical approach generally increases the dissolution rate of slag by adding additional alkali sources, thereby increasing the generation rate of early cementation products and the compressive strength of the matrix after hardening. For example, additional sodium hydroxide, sodium silicate, calcium oxide (magnesium hydroxide), magnesium oxide (including other mineral forms) are directly added to the material. Although the addition of strong alkali activators enables the cementitious materials to obtain higher mechanical properties, it also brings about problems such as high material cost, difficult to control workability, and high alkalinity causing harm to the human body and the environment. Therefore, it is necessary to develop more weak base activated cementitious systems to improve the early mechanical properties of cementitious materials without using strong bases such as sodium hydroxide and sodium silicate. Summary of the invention
[0004] In order to solve one of the above technical problems existing in the prior art, the present invention provides an alkali-activated gelling composition, a slag material and applications thereof.
[0005] A first aspect of the present invention provides an alkali-activated cementitious composition, comprising a cementitious material and sodium carbonate; wherein, in terms of weight percentage, the cementitious material comprises 50%-90% slag powder, 10%-40% silica-calcium slag and 0%-20% fly ash; in the composition, the weight of sodium carbonate accounts for 7%-10% of the total weight of the cementitious material.
[0006] According to some embodiments of the present invention, the alkali-activated gelling composition consists of a gelling material and sodium carbonate.
[0007] According to some embodiments of the present invention, the cementitious material includes, by weight percentage, 70%-90% (e.g., 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90% or any value therebetween) slag powder and 10%-30% (e.g., 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or any value therebetween) silica-calcium slag.
[0008] According to some embodiments of the present invention, the cementitious material includes, by weight percentage, 65%-75% slag powder and 25%-35% silica-calcium slag.
[0009] According to some embodiments of the present invention, the cementitious material comprises slag powder, calcium silicate slag and fly ash, and the mass ratio of the calcium silicate slag to the fly ash is ≥ 1. According to some embodiments of the present invention, the cementitious material comprises slag powder, calcium silicate slag and fly ash, and the mass ratio of the calcium silicate slag to the fly ash is (1-4):1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1 or any value therebetween.
[0010] According to some embodiments of the present invention, the cementitious material includes, by weight percentage, 50%-60% (e.g., 50%, 52%, 55%, 58%, 60% or any value therebetween) slag powder, 20%-40% (e.g., 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40% or any value therebetween) calcium-silicon slag and 10%-20% (e.g., 10%, 12%, 15%, 18%, 20% or any value therebetween) fly ash.
[0011] According to some embodiments of the present invention, the cementitious material includes, by weight percentage, 50%-55% slag powder, 20%-40% calcium silicate slag and 10%-20% fly ash.
[0012] According to some embodiments of the present invention, the cementitious material includes, by weight percentage, 50%-55% slag powder, 30%-40% calcium silicate slag and 10%-20% fly ash.
[0013] In the alkali-activated gelling composition of the present invention, the weight of sodium carbonate accounts for 7%-10% of the total weight of the gelling material, for example, it can be 7%, 8%, 9%, 10% or any value therebetween.
[0014] According to some embodiments of the present invention, the sodium carbonate is sodium carbonate powder. According to some embodiments of the present invention, the purity of the sodium carbonate powder is ≥95%.
[0015] In the present invention, sodium carbonate is used as an alkali activator, and calcium-silicon slag is introduced to enhance the early reaction rate of the sodium carbonate alkali slag material. The introduction of calcium-silicon slag not only effectively improves the early age problem of the sodium carbonate alkali-activated slag, but also can synergistically dispose of various types of waste under the ratio described in the present invention.
[0016] According to some embodiments of the present invention, the slag powder meets the following conditions: the specific surface area is not less than 400m 2 / kg, 3-day activity index>55%, 28-day activity index>100% (tested according to GB / T 18046-2017).
[0017] According to some embodiments of the present invention, the slag powder meets the following conditions: the specific surface area is not less than 360m 2 / kg, and turns red after being mixed with ethylene glycol-anhydrous ethanol-phenolphthalein solution and boiled (according to GB / T 176-2017).
[0018] According to some embodiments of the present invention, main components of the calcium-silicon slag include calcium carbonate, siliceous katoite, γ-dicalcium silicate, calcium hydroxide and sodium carbonate.
[0019] According to some embodiments of the present invention, the calcium-silicon slag is obtained by core sampling from a calcium-silicon slag dump, has an appearance color of gray or white, and has a pure white interior after being crushed, and does not contain obvious vegetation, soil or other organic matter.
[0020] According to some embodiments of the present invention, the calcium-silicon slag meets the following conditions: the loss on ignition of organic matter is less than 4%. According to some embodiments of the present invention, the calcium-silicon slag meets the following conditions: the specific surface area is greater than 500 m 2 / kg. According to some embodiments of the present invention, the calcium-silicon slag satisfies the following conditions: the pH value of the aqueous solution of the calcium-silicon slag is greater than 11.5. For example, after the solution obtained by mixing the calcium-silicon slag with deionized water at a weight ratio of 1:10 is centrifuged at 3000 rpm, the pH value of the supernatant is greater than 11.5. According to some embodiments of the present invention, the calcium-silicon slag satisfies the following conditions: in the nitrogen adsorption test, when the relative pressure P / P 0 When >0.4, an obvious hysteresis loop can be observed in its adsorption-desorption curve. According to some embodiments of the present invention, the calcium-silicon slag satisfies the following condition: the pores in the calcium-silicon slag should be mainly capillary pores.
[0021] According to some embodiments of the present invention, the fly ash activity index meets the requirements of GB / T 1596-2017 (≥70%), and at a replacement rate of 30%, the ratio of the fluidity of fly ash-cement paste to the fluidity of cement paste and the corresponding mortar fluidity ratio are greater than 1.
[0022] The second aspect of the present invention provides a slag material, the raw materials for preparing the slag material include the alkali-activated gelling composition described in the first aspect of the present invention, water, and optional standard sand.
[0023] According to some embodiments of the present invention, the slag material is prepared using the alkali-activated gelling composition described in the first aspect of the present invention, water, and optional standard sand as raw materials.
[0024] According to some embodiments of the present invention, the mass ratio of water to the alkali-activated gelling composition is (0.4-0.6): 1. According to some embodiments of the present invention, the mass ratio of water to the alkali-activated gelling composition is (0.45-0.55): 1. According to some embodiments of the present invention, the mass ratio of water to the alkali-activated gelling composition is (0.5-0.6): 1. In some embodiments, the mass ratio of water to the alkali-activated gelling composition is (0.5-0.55): 1. In some embodiments, the mass ratio of water to the alkali-activated gelling composition is 0.5: 1.
[0025] According to some embodiments of the present invention, the 3-day compressive strength of the slag material is greater than 20 MPa, and the 7-day compressive strength is greater than 35 MPa.
[0026] The third aspect of the present invention provides a method for preparing the slag material according to the second aspect of the present invention, comprising the following steps:
[0027] Mixing the alkali activated cementitious composition with water and optional standard sand to obtain slurry mortar;
[0028] The slurry mortar is injected into a mold, cured at 20-35° C., and hardened to obtain the slag material.
[0029] According to some embodiments of the present invention, the curing temperature is 20-25° C. According to some embodiments of the present invention, the curing time is 0.5-1 day.
[0030] The fourth aspect of the present invention provides use of the alkali-activated gelling composition described in the first aspect of the present invention or the slag material described in the second aspect of the present invention in building materials.
[0031] According to some embodiments of the present invention, the building material includes concrete and mortar.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention adds calcium silicate slag to the slag powder (and fly ash) solid waste cementitious material activated by weak alkali sodium carbonate, and synergistically activates the slag powder (and fly ash) with sodium carbonate, especially improving the early mechanical properties of the cementitious material.
[0034] 2. The present invention uses only one alkaline activator (weak alkaline sodium carbonate activator), without the need to use strong alkaline activators such as sodium hydroxide and sodium silicate, and without the need to add any highly corrosive and viscous alkaline chemicals. It can significantly improve the early strength of solid waste materials such as slag and fly ash at a higher water-solid ratio.
[0035] 3. The present invention improves the early strength of the sodium carbonate alkali-activated slag material while increasing the utilization rate of silicon-calcium slag solid waste and reasonably disposing of various solid wastes. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0037] The term "cementitious material" used in this application is also called cementing material, which refers to a substance that can be transformed from a slurry into a solid stone-like body under physical and chemical effects, and can be cemented with other materials to form a composite solid with a certain mechanical strength. Examples of cementitious materials commonly used in this field include: slag powder, fly ash, silica-calcium slag, lime, gypsum, cement, etc.
[0038] The specific surface area of the slag powder used in this application is ≥400m 2 / kg, 3d activity index>55%, 28d activity index≥100% (tested according to GB / T 18046-2017); or for specific surface area higher than 360m 2 / kg but less than 400m 2 / kg, turns red after being mixed and boiled with "ethylene glycol-anhydrous ethanol-phenolphthalein" solution (according to GB / T 176-2017).
[0039] The calcium-silicon slag used in the present application is finely ground gray or white dealkalized calcium-silicon slag, and the specific surface area of the calcium-silicon slag is greater than 500m 2 / kg, calcium silicate slag and water were mixed in a mass ratio of 1:10 and centrifuged, the pH value of the supernatant was >11.5, and the loss on ignition of calcium silicate slag due to organic matter was <4%; when the calcium silicate slag was subjected to nitrogen adsorption test, when the relative pressure P / P 0 When >0.4, an obvious hysteresis loop can be observed in its adsorption-desorption curve.
[0040] The fly ash activity index used in the present application meets the requirements of GB / T 1596-2017, and at a replacement rate of 30%, the ratio of the fluidity of fly ash-cement paste to that of cement paste and the ratio of the corresponding mortar fluidity are greater than 1.
[0041] The purity of the sodium carbonate powder used in the present application is ≥95%.
[0042] Comparative Example 1
[0043] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 450g of slag powder and 1350g of standard sand were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, and the test block could not be demolded after curing in a 20℃ curing box for 24 hours, and no compressive strength development was subsequently achieved.
[0044] Example 1
[0045] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 405g of slag powder, 45g of calcium silicate slag and 1350g of standard sand were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, and cured in a curing box at 20℃ for 24 hours. The test block was easy to peel off. After careful demolding, it continued to be wrapped and cured. The 3d compressive strength was 26MPa and the 7d strength was 38MPa.
[0046] Example 2
[0047] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 360g of slag powder, 90g of calcium silicate slag and 1350g of standard sand were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, and cured in a curing box at 20℃ for 24 hours. The test block was hard and easy to demould. It continued to be cured in the film curing box. The 3d compressive strength was 28MPa and the 7d strength was 40MPa.
[0048] Example 3
[0049] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 315g of slag powder, 135g of calcium silicate slag and 1350g of standard sand were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, and cured in a curing box at 20℃ for 24 hours. The test block was hard and easy to demould. It continued to be cured in the film curing box. The 3d compressive strength was 30MPa and the 7d strength was 37MPa.
[0050] Comparative Example 2
[0051] The experimental water-to-solid ratio was set to 0.5, and 36 g of sodium carbonate powder, 243 g of water, and 450 g of slag powder (specific surface area 370 m 2 / kg, heated with "ethylene glycol-ethanol-phenolphthalein" to turn red) and 1350g of standard sand, mix all the powders and water and stir slowly for 2 minutes, then stir quickly for 2 minutes. Pour the mixed slurry into a 40mm×40mm×40mm steel mold, wrap it with plastic film, and cure it in a curing box at 25℃ for 24 hours. The test block can be demoulded but is easy to peel off. Continue to wrap it in the curing box for curing. The 3d compressive strength is 16MPa and the 7d strength is 34MPa.
[0052] Example 4
[0053] The experimental water-to-solid ratio was set to 0.5, and 36 g of sodium carbonate powder, 243 g of water, and 405 g of slag (specific surface area 370 m 2 / kg, heated with "ethylene glycol-ethanol-phenolphthalein" to turn red) and 45g of silica-calcium slag and 1350g of standard sand, mix all the powders and water and stir slowly for 2 minutes, then stir quickly for 2 minutes. Pour the mixed slurry into a 40mm×40mm×40mm steel mold, wrap it with plastic film, and demould it after curing in a curing box at 20℃ for 24 hours, and continue to wrap it in a curing box for curing. The 3d compressive strength is 25MPa and the 7d strength is 37MPa.
[0054] Example 5
[0055] The experimental water-to-solid ratio was set to 0.5, and 36 g of sodium carbonate powder, 243 g of water, and 360 g of slag powder (specific surface area 370 m 2 / kg, heated with "ethylene glycol-ethanol-phenolphthalein" to turn red) and 90g of silica-calcium slag and 1350g of standard sand, all powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, cured in a 20℃ curing box for 24 hours, demolded, and continued to be cured in a film curing box. The 3d compressive strength was 27MPa and the 7d strength was 36MPa.
[0056] Example 6
[0057] The experimental water-to-solid ratio was set to 0.5, and 36 g of sodium carbonate powder, 243 g of water, and 315 g of slag (specific surface area 370 m 2 / kg, heated with "ethylene glycol-ethanol-phenolphthalein" to turn red), 135g of silicon-calcium slag and 1350g of standard sand, mix all the powders and water and stir slowly for 2 minutes, then stir quickly for 2 minutes. Pour the mixed slurry into a 40mm×40mm×40mm steel mold, wrap it with plastic film, cure it in a 20℃ curing box for 24 hours, remove it from the mold, continue to wrap it with film and cure it in a curing box, and the 3d compressive strength is 29MPa and the 7d strength is 36MPa.
[0058] Comparative Example 3
[0059] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 225g of slag powder, 225g of fly ash and 1350g of standard sand were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, and cured in a curing box at 20℃ for 24 hours. It could not be demoulded, and there was no subsequent strength development.
[0060] Example 7
[0061] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 225g of slag powder, 180g of fly ash, 45g of calcium silicate slag and 1350g of standard sand were weighed. All powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, and cured in a curing box at 20℃ for 24 hours. It could not be demoulded, and there was no subsequent strength development.
[0062] Example 8
[0063] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 225g of slag powder, 135g of fly ash, 90g of calcium silicate slag and 1350g of standard sand were weighed. All powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, and cured in a curing box at 20°C for 24 hours. It could not be demoulded, and there was no subsequent strength development.
[0064] Example 9
[0065] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 225g of slag powder, 135g of calcium silicate slag, 90g of fly ash and 1350g of standard sand were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, cured in a curing box at 20℃ for 24h, demolded, and continued to be cured in a film curing box. The 3d compressive strength was 27MPa and the 7d strength was 39MPa.
[0066] Example 10
[0067] The experimental water-solid ratio was set to 0.5, and 36g of sodium carbonate powder, 243g of water, 225g of slag powder, 180g of calcium silicate slag, 45g of fly ash and 1350g of standard sand were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 40mm×40mm×40mm steel mold, wrapped with plastic film, cured in a curing box at 20℃ for 24h, demolded, and continued to be cured in a film curing box. The 3d compressive strength was 29MPa and the 7d strength was 36MPa.
[0068] Comparative Example 4
[0069] The experimental water-solid ratio was set to 0.5, and 8g of sodium carbonate powder, 54g of water, and 100g of slag powder were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 30mm×30mm×30mm steel mold, wrapped with plastic film, and cured in a curing box at 20℃ for 24 hours. It could not be demolded, and there was no subsequent strength development.
[0070] Embodiment 11
[0071] The experimental water-solid ratio was set to 0.5, and 8g of sodium carbonate powder, 54g of water, 90g of slag powder and 10g of calcium silicate slag were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 30mm×30mm×30mm steel mold, covered with plastic film, and cured in a curing box at 20℃ for 24 hours. It was easy to peel off and demouldable. The 3d compressive strength was 24MPa and the 7d strength was 33MPa.
[0072] Example 12
[0073] The experimental water-solid ratio was set to 0.5, and 8g of sodium carbonate powder, 54g of water, 80g of slag powder and 20g of calcium silicate slag were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 30mm×30mm×30mm steel mold, covered with plastic film, and cured in a curing box at 20℃ for 24 hours. It was easy to peel off and demouldable. The 3d compressive strength was 26MPa and the 7d strength was 34MPa.
[0074] Comparative Example 5
[0075] The experimental water-solid ratio was set to 0.5, and 8g of sodium carbonate powder, 54g of water, 60g of slag powder and 40g of fly ash were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 30mm×30mm×30mm steel mold, wrapped with plastic film, and could not be demolded after curing in a curing box at 20℃ for 24 hours, and no subsequent strength development was achieved.
[0076] Embodiment 13
[0077] The experimental water-solid ratio was set to 0.5, and 8g of sodium carbonate powder, 54g of water, 60g of slag powder, 30g of fly ash and 10g of calcium silicate slag were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 30mm×30mm×30mm steel mold, wrapped with plastic film, and could not be demolded after curing in a curing box at 20°C for 24 hours, and no subsequent strength development was achieved.
[0078] Comparative Example 6
[0079] The experimental water-solid ratio was set to 0.5, and 8g of sodium carbonate powder, 54g of water, 50g of slag powder and 50g of fly ash were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 30mm×30mm×30mm steel mold, wrapped with plastic film, and could not be demolded after curing in a curing box at 20℃ for 24 hours, and no subsequent strength development was achieved.
[0080] Embodiment 14
[0081] The experimental water-solid ratio was set to 0.5, and 8g of sodium carbonate powder, 54g of water, 60g of slag powder, 20g of fly ash and 20g of calcium silicate slag were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 30mm×30mm×30mm steel mold, covered with plastic film, and demolded after curing in a curing box at 20℃ for 24 hours. The 3d compressive strength was 24MPa and the 7d strength was 37MPa.
[0082] Embodiment 15
[0083] The experimental water-solid ratio was set to 0.5, and 8g of sodium carbonate powder, 54g of water, 60g of slag powder, 10g of fly ash and 30g of calcium silicate slag were weighed. All the powders and water were mixed and stirred slowly for 2 minutes, and then stirred quickly for 2 minutes. The mixed slurry was poured into a 30mm×30mm×30mm steel mold, covered with plastic film, and demolded after curing in a curing box at 20℃ for 24 hours. The 3d compressive strength was 25MPa and the 7d strength was 35MPa.
[0084] The properties of the slag materials obtained in the embodiments of the present invention and the comparative examples are shown in Table 1:
[0085] Table 1
[0086]
[0087] It can be seen from Table 1 that when the cementitious material contains slag powder and calcium silicate slag, the prepared slag material is easy to demould and has good compressive strength. When the cementitious material contains slag powder, calcium silicate slag and fly ash, when the amount ratio of calcium silicate slag to fly ash is ≥1, the prepared slag material is easy to demould and has good compressive strength.
[0088] Note: The compressive strength described in the embodiments of the present invention and the comparative examples is tested according to the Chinese national standard GB / T17671-2021.
[0089] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An alkali-activated gelling composition, comprising a gelling material and sodium carbonate; in, In terms of weight percentage, the cementitious material is composed of 50%-60% slag powder, 20%-40% calcium silicate slag and 10%-20% fly ash; in the composition, the weight of sodium carbonate accounts for 7%-10% of the total weight of the cementitious material; The main components of the calcium-silicon slag include calcium carbonate, siliceous katoite, gamma-dicalcium silicate, calcium hydroxide and sodium carbonate.
2. The alkali-activated gelling composition according to claim 1, characterized in that: In terms of weight percentage, the cementitious material is composed of 50%-55% slag powder, 20%-40% calcium silicate slag and 10%-20% fly ash, and the sum of the amounts of the above components is 100%.
3. The alkali-activated gelling composition according to claim 1 or 2, characterized in that: The slag powder meets the following conditions: the specific surface area is not less than 400m 2 / kg, 3-day activity index>55%, 28-day activity index>100%; or, The slag powder meets the following conditions: the specific surface area is not less than 360m 2 / kg, and turns red after being mixed with ethylene glycol-anhydrous ethanol-phenolphthalein solution and boiled.
4. The alkali-activated gelling composition according to claim 1 or 2, characterized in that: The calcium-silicon slag meets the following conditions: the loss on ignition of organic matter is less than 4%, and / or the specific surface area is greater than 500 m 2 / kg, and / or, the pH value of the aqueous solution of the silica-calcium slag is >11.
5.
5. The alkali-activated gelling composition according to claim 1 or 2, characterized in that: The fly ash activity index meets the requirements of GB / T 1596-2017, and at a replacement rate of 30%, the ratio of the fluidity of fly ash-cement paste to the fluidity of cement paste and the ratio of the corresponding mortar fluidity are greater than 1.
6. A slag material, wherein the raw materials for preparing the slag material include the alkali-activated gelling composition according to any one of claims 1 to 5, water and standard sand.
7. The slag material according to claim 6, characterized in that: The mass ratio of water to the alkali-activated gelling composition is (0.5-0.6):
1.
8. A method for preparing the slag material according to claim 6 or 7, comprising the following steps: Mixing the alkali-activated cementitious composition with water and standard sand to obtain slurry mortar; The slurry mortar is injected into a mold, cured at 20-35° C., and hardened to obtain the slag material.
9. Use of the alkali-activated gelling composition according to any one of claims 1 to 5 or the slag material according to claim 6 or 7 in building materials.
Citation Information
Patent Citations
Cementing material containing silicon-calcium slag and preparation method thereof
CN104129934A